The knowledge, attitudes and practices on HIV/AIDS among peer educators in the Limpopo Department of Agriculture - Shipalana, Pearl Nkhenshani (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2009.